"Indians don't get transplants": dialysis patient experience and political economic barriers to transplantation on the Pine Ridge Indian Reservation - Reedy, Julia, author; Magennis, Ann, advisor; Browne, Katherine, committee member; Kwiatkowski, Lynn, committee member; Long, Marilee, committee member (Colorado State University. Libraries, 2020)
The Oglala Lakota people of the Pine Ridge Indian Reservation have been plagued with poor kidney health due to political economic factors such as poverty, discrimination, unemployment, and limited food access. This poor health, exemplified in high rates of end-stage renal disease (ESRD), has created a population of patients that face daily challenges associated with dialysis treatment. Many of these patients would prefer kidney transplantation as treatment for their ESRD; however, a multitude of structural, institutional, educational, and biological barriers create obstacles that most find too difficult to overcome. This thesis explores the lived realities of dialysis patients on the Pine Ridge Indian Reservation and the structural challenges these patients face in accessing kidney transplantation. With dialysis patients often overlooked in terms of research and healthcare initiatives, this research provides the platform for patients to tell their stories, share their experiences, and advocate for their right to health and dignity. This applied anthropological research seeks to tackle the real-world issues of transplantation access among the Oglala Lakota population living on Pine Ridge. Therefore, the goal of this research is to both identify existing barriers as well as posit solutions that will help with the mediation of these barriers to improve access to kidney transplantation. Drawing on ethnographic methods such as participant observation and semi-structured interviews, this research attempts to provide an insider's perspective to dialysis challenges and the experiences of patients suffering from end-stage renal disease. This research focuses on three primary areas of interest. The first seeks to illuminate the dialysis patient experience, daily activities and limitations, and emotional responses to an end-stage renal disease diagnosis. This line of research serves as a window into the lives of dialysis patients, providing an emic or insider's perspective into the difficulties and challenges these individuals face. The second primary area of interest examines systems of belief and support present on the reservation represented by traditional Lakota belief systems and Christianity. Each of these systems functions to support patients during periods of hardship, but also plays an influencing role in healthcare decision-making. The third research focus explores the myriad barriers that inhibit access to kidney transplantation among the Oglala Lakota people. The distal and proximal barriers imposed on patients can be categorized as structural, institutional, educational, or biological, affecting patients in different areas and at different times in their lives. Using critical medical anthropology and structural vulnerability as the theoretical basis for data interpretation, the different structural levels of the healthcare system are examined. Each of these levels provides explanatory power regarding the regulation, influences, and pressures applied by the larger system on the individual. The critical medical anthropology approach also demonstrates a clear mismatch between the ideal transplantation process and the real-world capabilities of Oglala Lakota patients. To mediate identified barriers and align these mismatched systems, I provide specific recommendations for policy and practice that can be implemented to improve patient health and facilitate access to transplantation for those who seek it.
Indians don't get transplants: dialysis patient experience and political economic barriers to transplantation on the Pine Ridge Indian Reservation
Keywords: diabetes; health disparities; kidney transplantation; dialysis; American Indian; healthcare access